PENGARUH PERUBAHAN SATUAN TIMING BUKA TUTUP KATUP TERHADAP KONSUMSI BAHAN BAKAR DAN EMISI GAS BUANG PADA MESIN SEPEDA MOTOR SHOGUN 125cc - M. Noor; Misbachudin , (JMIO, 2019)
Motorcycle is a means of transportation that is driven by an engine. This type is widely used because the price is relatively cheap. Generally, motorcycles use gasoline fuel so that the principal works is no different from motorcycles in cars. The 4-stroke combustion motor is an internal combustion engine, which in one combustion cycle will experience four piston steps, producing one effort step or one fuel combustion. A valve is an engine component that functions as a passageway of a mixture of fuel and air entering the cylinder or as a passageway from the combustion gas exiting the cylinder. Changing the valve timing unit has various effects on fuel consumption and exhaust emissions. So, from the results of research that has been done shows that advancing the unit of valve opening and opening time produces the most economical fuel consumption that is, 0.0663570 ml / sec and the exhaust gas CO2 = 0.4%, CO = 0.05%, HC = 65%, O2 = 20.90%. Keywords: combustion engine, fuel consumption, exhaust emissions, valve